AN OVERVIEW OF THE JUDICIARY AGAINST THE MARKETING AUTHORIZATION WHICH WAS REPEALED OF TRADITIONAL MEDICINAL PRODUCTS BRAND PI KANG SHUANG IN SAMARINDA BASED ON LAW NO. 36 OF 2009 ON HEALTH - Brigitta, Bella (Legal Standing : Jurnal Ilmu Hukum, 2018)
In traditional medical products brands Pi Kang Shuang, experiencing problems with marketing authorization that are not listed on the traditional medical products Pi Kang Shuang brands, there are two problems in this thesis any reason What are the factors still circulating products not my traditional medical Pi Kang Shuang brands do not have a marketing authorization in Samarinda and how control center taken for the Food and Drug Administration's efforts (BBPOM) on the circulation and trafficking in conventional drugs that have not been recorded in the city of Samarinda. The purpose of this study was to determine the cause of traditional medicines that were not registered in the city of Samarinda trading and identify enforcement conducted by the Food and Drug Administration Center (BBPOM) in Samarinda for violating trading traditional medicines that are not registered and do not have BPOM number in the city of Samarinda. Writing method that I use is an experimental research done by direct observation of spaciousness for data collection, processing and analysis of law data on enforcement brand traditional medicinal Pi Kang Shuang products who do not have marketing authorization, which is where the study's authors are still trading products exist traditional medical Pi Kang Shuang brands. The concept of the book is provided to improve the supervision of the Centre for Food and Drug Control, provide guidance on traditional medicine which has a legitimacy that would come at a time when there is no longer in traditional medicine has not traded for marketing authorization